The Institutionalization of Suffering: Embodied Inhabitation and the Maintenance of Health and Safety in E-waste Recycling. Issue 5 (June 2018) - Stowell, Alison F.; Warren, Samantha
In this article, we put forward the concept of 'embodied inhabitation' to bring a bodily and material perspective to bear on institutional maintenance. Using an 'inhabited institutions' framework, and drawing on autoethnographic, visual data, we develop a strategy of empathizing with field research participants that blurs the boundaries between human and non-human, social and material, and cultural and biological in understanding the embodied micro-level, situated interactions that maintain the institutional status quo. These have hitherto been overlooked in studies of institutional maintenance and institutional theory more broadly. Empirically, we explore how organizational imperatives designed to uphold the institution of the 'safe system of work' required by health and safety law in the United Kingdom play out in the course of the everyday work of e-waste recycling workers. Three vignettes relating to an overarching theme of 'suffering' consider institutional inhabitation as micro-level embodied interactions, and we show how socio-embodied discourses of commitment, skill and (working-class) masculinities legitimate the normalization of waste workers' suffering, which in turn maintains institutionalized ideas of health and safety at work. We conclude by reflecting on the value of employing an 'embodied inhabitation' approach in other institutional settings.